Limiting Factors Affecting the Efficiency of Rainwater Harvesting in Karst Telaga Systems: A Case Study in Gunungkidul, Indonesia - Utama, Tri Budi; Bisri, M.; Prayogo, Tri Budi; Haribowo, Riyanto; Limantara, Lily Montarcih (Engineering, Technology & Applied Science Research, 2026)
This study evaluates the dominant limiting factors that affect the efficiency of Rainwater Harvesting (RWH) systems in karst telaga environments of the Semanu and Tepus districts, Gunungkidul, Indonesia. A structured analytical framework was developed based on three interrelated system components—harvesting, storage, and utilization—to assess both theoretical and actual system performance. Field measurements from 40 telaga lakes were integrated with climatological, hydrological, and geological data to quantify performance gaps and identify dominant loss mechanisms. The results indicate a substantial discrepancy between the theoretical harvesting potential (20.85%) and actual system efficiency (6.09%). High infiltration rates associated with karst characteristics significantly reduce effective runoff, while evaporation losses of 5–7 mm/day and average sedimentation levels of 48.25% decrease storage capacity to approximately 35% of its initial design. In addition, distribution inefficiencies further constrain effective water utilization for irrigation. These interacting loss mechanisms collectively limit storage duration to only 2–3 months after the rainy season. By systematically linking empirical findings to parameter prioritization, this study provides a structured analytical model for diagnosing efficiency gaps in karst-based RWH systems. The findings support targeted optimization strategies focused on loss reduction, storage rehabilitation, and distribution improvement. The proposed framework contributes a replicable approach for evaluating rainwater harvesting efficiency in tropical karst regions facing seasonal water scarcity.